Technological Disease and Illness in Modern Society - Phetcharaburanin, Prisana (Journal of Advanced Development in Engineering and Science, 2023)
Even Information and communication technologies have been changing the world and giving us a lot of benefit but too much of using technologies can affect physical body and mind. For physical body, sitting and watching monitor for too long can lead user to vitreous floater and cumulative trauma disorders. Moreover, according to recent research, Wi-Fi can also have a negative effect on 5 - 10 years old children?s brain. For Psychological perspective, using too much of technologies can cause a serious mental illness such as Nomophobia and can affect 6 - 7 years old children’s mental health in the long run. The only best way to prevent these technological disease and illness is encouraging people to learn and understand to negative effect of over using technologies and learn how to prevent or avoid those effects.